2005
DOI: 10.1007/s10493-005-3262-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the bm86 Gene in South American Strains of the Cattle Tick Boophilus microplus

Abstract: Thirty Boophilus microplus strains from various geographic regions of Brazil, Argentina, Uruguay, Venezuela and Colombia were analyzed for the bm86 and bm95 gene. A fragment of cDNA of 794 base pairs of the parasite larvae, included between nucleotides 278-1071s, was amplified and cloned on the pGEM-T vector. Two random clones were sequenced for each population and the nucleotides 278-1071 and predicted amino acid sequences compared with the bm86 and bm95 genes. Variations from 1.76 to 3.65% were detected in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 22 publications
2
21
0
4
Order By: Relevance
“…The number and location of isolates selected reflects the proportion of current outbreaks in their respective counties, as well as the number of female ticks submitted through the CFTEP that were available for oviposition. This number of isolates is also comparable to that used in previous descriptions of Bm86 geographic sequence variability [11]. The majority of documented infestations in South Texas are R. microplus , and this is reflected in the number of isolates sequenced: 24 R. microplus and 3 R. annulatus (Table 1).…”
Section: Resultssupporting
confidence: 81%
“…The number and location of isolates selected reflects the proportion of current outbreaks in their respective counties, as well as the number of female ticks submitted through the CFTEP that were available for oviposition. This number of isolates is also comparable to that used in previous descriptions of Bm86 geographic sequence variability [11]. The majority of documented infestations in South Texas are R. microplus , and this is reflected in the number of isolates sequenced: 24 R. microplus and 3 R. annulatus (Table 1).…”
Section: Resultssupporting
confidence: 81%
“…This sequence was not found in any of the five sequenced clones and may be less abundant, have been the result of alternative splicing or represent an allele which was lost in the R. microplus tick population since the source material was collected several generations earlier. The presence of Bm86 alleles within the same tick population has been previously reported [18]. Two alleles, Ra86-1 and Ra86-2, were also found to be transcribed in the midgut of R. appendiculatus females.…”
Section: Discussionsupporting
confidence: 70%
“…(B.) microplus, Sossai et al (2005) suggested that geographic isolation is not the sole determinant of genomic variation. It has been suggested that diversity greater than 3% in amino acid sequence between the recombinant antigen and native Bm86 protein in target tick populations results in vaccination inefficiencies .…”
Section: Introductionmentioning
confidence: 99%